(untitled) (Bangladesh Journal of Public Administration, 2022)
Although Bangladesh has a higher risk of accidents involving pedestrians, safety culture is vital in reducing unintentional deaths and injuries, generally in developing countries. The promotion of a pedestrian safety culture has received little attention. This study looked into Bangladeshi pedestrians’ present attitudes toward and understanding of safety and related activities. Using an online-based structured questionnaire with 16 items relevant to safety attitude, awareness, and actions, a cross-sectional survey of 320 randomly chosen Bangladeshi citizens was carried out. According to the study, pedestrians’ safety attitudes, awareness, and behaviour levels are insufficient. It was revealed that safer pedestrian actions were connected with positive attitudes toward traffic safety. Males, younger respondents and respondents with less education reported engaging in riskier behaviours and having more risky views regarding traffic safety. In order to strengthen and promote a safety culture among Bangladeshi walkers, it is advised that various safety education courses, training, and awareness programs be implemented. The safety culture of road safetyof Bangladeshi people needs to be investigated. Road Safety,